Synthesizing an Angklung - Anis Haron; Norfarizah Mohd Bakhir; Low Kok On (2018)
This paper considers the spectral properties of the Angklung, an Indonesian musical instrument made from bamboo tubes that is popular throughout Southeast Asia. We have chosen three most significant partials from both bamboo tubes on each strike directions. We have developed an additive synthesis Pure Data implementation for synthesizing the Angklung, which produces a tone that is very similar to the original instrument.